Using Ultrasonography and Doppler Application for Evaluating Vascular Axes and Prevention of Compartmental Syndrome (International Journal of Medical and Surgical Sciences, 2016)
Ultrasonography is with adequate training, a fast and effective evaluation method in emergency departments. Peripheral vascular injury is frequent in trauma and should have a rapid diagnosis and treatment, as risks include: open sores, bleeding; closed injuries and compartmental syndrome. Prompt evaluation of the integrity in the vascular tree becomes important in preventing events that require surgical intervention (repair and / or fasciotomy). The aim of this work is to demonstrate the usefulness of knowledge of peripheral vascular tree, ultrasound evaluation and Doppler for peripheral vascular trauma management, using checklists for the systematic evaluation of the vasculature. Systematic evaluations were realized in 10 general surgery residents. Initially, using inanimate and animate models which were then evaluated in trauma situations. Divided into periods (February / April 2016 – May/August 2016). The findings with previous criteria made the verification list and subsequent connection with the development of compartment syndrome that were established by correlation. Evaluation animated models: 1st assessment: Recognition of structures>60 % =6 residents. > 80 % =4 residents. The 2nd assessment: Recognition of structures > 60 % = 3 residents. > 80 % = 7 residents. In the care of multiple trauma: recognition structures > 60% =3 residents. >80 % =7 residents. Patients at risk for compartmental syndrome (n=77) =11 (14.78 %). Resolution: Vascular Lesion 1 (1.3 %) compartmental syndrome: 1 (1.3 %) with surgical resolution. The use of ultrasonography and Doppler for peripheral vascular evaluation is useful for early recognition of risk from developing a single vascular lesion, to compartmental syndrome. The use of the checklists during simulation for the generation of criteria is useful in the training of surgical residents.